Estudio de mercado de viviendas tipo medio para la creación de Empresas constructoras Inmobiliarias estudio caso para la Ciudad de Santa Rosa - Monserrate Arellano, Wilmer Dante (2016)
Supply and demand average homes in the city of Santa Rosa, is conducive to creating real estate construction companies. The overall objective is to investigate the supply and demand for residential housing across the city of Santa Rosa, to encourage the creation of Real Estate Construction Companies; with specific objectives such as: determining the parameters for the supply and demand for housing in cities of up to 100,000 inhabitants, determine the Supply and Demand of Housing Font of the city of Santa Rosa and its impact on the creation of Real Estate and Construction Companies Design a Housing Construction Company by reference to a Housing Market Study Font. A research methodology with qualitative and quantitative approach was raised. The type of research was framed in the field research and literature documentary. The research was exploratory, descriptive, correlational and explanatory kind. The research design was transversal. Reporting mechanisms are based on survey, interviews and observation. The results of the analysis of supply and demand for average homes in the city of Santa Rosa, indicate that there is a 29% of users tenants equivalent to 1076 a total of 3707 users requiring tenants story single-family homes, 60 to 80 m2 of construction, with amounts of $ 30,000 to $ 40,000; in the middle there is an offer of 287 homes, distributed in 200 of a plant worth $ 87 to $ 24,000 and two plants worth $ 60,000. It is evident that there is a shortage of home ownership tenure of 789 homes. To meet this demand the creation of a housing construction company designed a strategic plan that will address this housing need arises.